Assessing Knowledge Production for Agrosilvopastoral Systems in South America - Soler Esteban, Rosina Matilde; Peri, Pablo Luis; Bahamonde, Héctor Alejandro; Gargaglione, Veronica Beatriz; Ormaechea, Sebastián Gabriel; Huertas Herrera, Alejandro; Sánchez Jardón, Laura; Lorenzo, Cristian; Martínez Pastur, Guillermo José (2018)
In recent decades agroforestry has undergone significant development in Latin America. South America generates the most scientific research on the topic in the region. We conducted a comprehensive review and analysis of knowledge production for South American agroforestry that includes livestock grazing, known as agrosilvopastoralism (AS), examining how different sociopolitical factors such as sources of funding, institutional priorities, and international cooperation can bias the direction and objectives of scientific research. We assessed the major attributes of scientific publications on the topic (25 articles per country; overall n = 210) and the potential factors underlying the processes of research and development in the region. The tree component was the most studied, while the livestock component received less attention. Studies were mainly focused on the production of goods and services (monetary or nonmonetary approaches), except in Brazil, where conservation was the major study objective. Stakeholders were involved in more than half of the studies (60%), and they were mostly ranchers and local producers. More than half (70%) of the studies offered recommendations based on their results, and such recommendations were mostly concerned with the management of agrosilvopastoral system components. In general, studies were led just as often by local as foreign first authors and coauthored by more than three people as part of interinstitutional working groups. Brazil, Argentina, Colombia, and Chile had more frequent cooperation among institutions and countries but mainly used their own funding. In contrast, Bolivia, Ecuador, and Peru had almost 100% of their studies supported by foreign countries (North America and Europe). Countries with greater internal funding of research generated more long-term studies. Besides this, two clear trends were detected: 1) conservation and social aspects were mainly supported by sources from external countries led by foreign principal investigators, and 2) production issues were supported from sources within countries and supported high levels of cooperation among institutions.